A user-friendly and scalable process to prepare a ready-to-use inactivated vaccine: The example of heartwater in ruminants under tropical conditions. Issue 5 (29th January 2015) - Marcelino, Isabel; Lefrançois, Thierry; Martinez, Dominique; Giraud-Girard, Ken; Aprelon, Rosalie; Mandonnet, Nathalie; Gaucheron, Jérôme; Bertrand, François; Vachiéry, Nathalie
Abstract The use of cheap and thermoresistant vaccines in poor tropical countries for the control of animal diseases is a key issue. Our work aimed at designing and validating a process for the large-scale production of a ready-to-use inactivated vaccine for ruminants. Our model was heartwater caused by the obligate intracellular bacterium Ehrlichia ruminantium (ER). The conventional inactivated vaccine against heartwater (based on whole bacteria inactivated with sodium azide) is prepared immediately before injection, using a syringe-extrusion method with Montanide ISA50. This is a fastidious time-consuming process and it limits the number of vaccine doses available. To overcome these issues, we tested three different techniques (syringe, vortex and homogenizer) and three Montanide ISA adjuvants (50, 70 and 70M). High-speed homogenizer was the optimal method to emulsify ER antigens with both ISA70 and 70M adjuvants. The emulsions displayed a good homogeneity (particle size below 1 μm and low phase separation), conductivity below 10 μS/cm and low antigen degradation at 4 °C for up to 1 year. The efficacy of the different formulations was then evaluated during vaccination trials on goats. The inactivated ER antigens emulsified with ISA70 and ISA70M in a homogenizer resulted in 80% and 100% survival rates, respectively. A cold-chain rupture assay using ISA70M+ER was performed to mimic possible field conditions exposing the vaccine at 37 °C for 4 days before delivery. Surprisingly, the animal survival rate was still high (80%). We also observed that the MAP-1B antibody response was very similar between animals vaccinated with ISA70+ER and ISA70M+ER emulsions, suggesting a more homogenous antigen distribution and presentation in these emulsions. Our work demonstrated that the combination of ISA70 or ISA70M and homogenizer is optimal for the production of an effective ready-to-use inactivated vaccine against heartwater, which could easily be produced on an industrial scale.